Cursos superiores de tecnologia e perfil econômico regional: análise de egressos do IFSP Piracicaba - Aranha, Cinthia Bomtorin (2020)
The Federal Institutes, instituted through Law 11.892 of 2008, bring a new model for the development of professional education in Brazil. Organized in a multicampi structure and offering basic, professional and higher education, the Federal Institutes have the characteristics and purposes of meeting, through the dimensions of teaching, research and extension, social demands and regional specificities, with a focus on local socioeconomic development, regional and national, and consolidation and strengthening of the productive, social and cultural arrangements of the localities in which they operate. Thus, the present study aims to analyze the insertion of the IFSP Piracicaba in the local and regional economic profile, based on the analysis of graduates from the Higher Technology Courses. For this, the research carried out a diagnosis of the economic-productive profile of Piracicaba and region, identifying the most dynamic sectors of the economy; identified the teaching, research and extension activities developed by IFSP Piracicaba analyzing the local and regional insertion of the institution; identified the professional profiles expected by the IFSP for those graduating from the Higher Technology Courses of the Federal Institute of Education, Science and Technology of São Paulo, Campus Piracicaba, through documentary analysis and interviews with agents representing the courses and the institution; and conducted research with graduates of the Higher Technology Courses in Analysis and Development of Systems and Industrial Automation in order to raise opinions on the training obtained, professional exercises in the area of training, places of origin and current professional practice, suggestions and criticisms. As a result, the characteristics of the two profiles of graduates were identified, identification of the predominance of positive opinions regarding the quality of the courses, the theoretical and practical classes offered by the institution, positive percentages in relation to professional practice with direct or partial relationship in the area of training and professional retention of graduates by the municipality of Piracicaba and region, as well as suggestions for improvements to the actions developed by the institution.